The Believer and the Modern Study of the Bible - Ganzel, Tova; Brandes, Yehuda; Deutsch, Chayuta (Academic Studies Press, 2019)
The essays in this volume address the conundrum of how Jewish believers in the divine character of the Sinaitic revelation confront the essential questions raised by academic biblical studies. The first part is an anthology of rabbinic sources, from the medieval period to the present, treating questions that reflect a critical awareness of the Bible. The second part is a series of twenty-one essays by contemporary rabbis and scholars on how they combine their religious beliefs with their critical approach to the Bible.